Gestão Estratégica: a toxicomania organizacional e a naturalização do sofrimento no trabalho - Silva, Guilherme Elias da; Hashimoto, Francisco [UNESP] (My University, 2012)
The general purpose of this study was a reflexive-theoretical analysis, based on the authors of Psycho-Sociology, seeking to understand how to establish working relationships in organizations considered strategic in the contemporary world. To do so, we identify the strategies that these organizations use to hold the individual in theirs meshes of power, emphasizing the effects of the psychological dynamics and the illusion of “drug organization”. Finally, we elucidated some of the major diseases related to working in organizations with strategic management model, which reflect the violence imposed by managerial policy that promotes a moral harassment and naturalization of suffering at work.

O objetivo geral deste estudo foi realizar uma análise teórico-reflexiva, fundamentada em autores da psicossociologia, buscando compreender como se estabelecem as relações de trabalho nas organizações consideradas estratégicas no mundo contemporâneo. Para tanto, procuramos identificar as estratégias que tais organizações utilizam para prender o indivíduo em suas malhas de poder, enfatizando os efeitos da dinâmica psicológica e a ilusão da “droga organização”. Por fim, foram elucidadas algumas das principais patologias decorrentes do trabalho nas organizações com modelo de gestão estratégica, as quais traduzem a violência ali imposta pela política gestionária que promove uma moral do assédio e a naturalização do sofrimento no trabalho.
Strategic management: organizational toxicomany and naturalization of suffering at work
Keywords: Psycho-Sociology; Work; Strategic organizations; Toxicomany; Suffering; Psicossociologia; Trabalho; Organizações estratégicas; Toxicomania; Sofrimento